Systematic Literature Review: The Role of Innovation and Competitive Advantage of Micro, Small, and Medium Enterprises as Mediation Variables - Munawir Nasir; Mts Arief; Firdaus Alamsjah; Elidjen Elidjen (PT Mattawang Mediatama Solution, 2024)
Systematic Literature Review (SLR), which focuses on the role of innovation and competitive advantage as mediators of various factors on the performance of Micro, Small, and Medium Enterprises (MSMEs), is still relatively rare. Therefore, this study aimed to determine the factors that affect competitive advantage and the role of innovation mediation and competitive advantage in influencing MSMEs performance. This study utilized Google Scholar as a database. Of 500 studies, 400 were excluded according to the title and abstract, and 100 were screened for eligibility, resulting in 41 studies included for review. This study showed that there were 45 factors that affected competitive advantage and 15 factors that affected sustainable competitive advantage. This study also found that innovation variables, including marketing innovation, innovation, green innovation, and corporate open innovation, mediated various factors influencing competitive and sustainable competitive advantages. Also, competitive advantage was able to mediate the relationship between several factors that affected the performance of MSMEs. These findings provided a reference for future research to analyze innovation as a mediating variable for the relationship of various factors to competitive advantage. This finding also provides information that for MSMEs to survive in globalization, they should have a competitive advantage to be competitive. Thus, the factors in this study can be used to strengthen the competitive advantage of MSMEs and improve their performance.